(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This research studied many types of concrete strengthening by using CFRP-sheet and CFRP-bar. Finite element modelling was created by using Abaqus 6.14 program. The control frame was calibrated with an experimental specimen, which tested under 2-points load up to failure. Model verification including ultimate load, maximum mid span deflection, mode failure. Model Convergence study was studied. Numerical results showed that using CFRP- sheet increasing ultimate load about (25%) compared with the control specimen. However, Using EBROG and EBRIG techniques increasing ultimate load about (4.7 %, 28.50 %) respectively. Strengthening frame with one and two CFRP bars increasing ultimate load about (38.8%, 20.47 %) respectively. On the other hand, Frame reinforced with two and three CFRP bars (without steel reinforcement) increased ultimate load about (3.60 %, 18.25 %).